Qualification of family health program professionals in brief diagnosis and intervention strategies for problematic alcohol use - Corradi-Webster, Clarissa M.; Minto, Elaine C.; Aquino, Fabrízia Maria C. de; Abade, Flávia; Yosetake, Lincoln Luiz; Gorayeb, Ricardo; Laprega, Milton Roberto; Furtado, Erikson Felipe (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2005)
With a view to preventing problematic alcohol use, the WHO developed brief intervention strategies (BDIS), disseminated in Brazil, since 2002, by PAI-PAD/WHO of the FMRP-USP. This study aimed to evaluate the benefits of BDIS training with the use of focal groups for FHP teams. The group profile reflected the distribution observed during training (60% agents, 85% women, and 51% adults under 35). The identified benefits were related to the cognitive and behavior change objectives: questioning of stereotypes; attention to systematic research and alcohol dependence seen as a disease. The professionals identified breaking stereotypes and understanding drinking patterns as training benefits, which favored the implementation of the BDIS